2020
DOI: 10.1007/s00167-020-06035-z
|View full text |Cite
|
Sign up to set email alerts
|

Hip capsular strain varies between ligaments dependent on both hip position- and applied rotational force

Abstract: Purpose To noninvasively characterize the ligament strain in the hip capsule using a novel CT-based imaging technique. Methods The superior iliofemoral ligament (SIFL), inferior iliofemoral ligament (IIFL), ischiofemoral ligament (IFL) and pubofemoral ligament (PFL) were identified and beaded in seven cadavers. Specimens were mounted on a joint motion simulator within an O-arm CT scanner in − 15°, 0°, 30°, 60°, and 90° of flexion. 3 Nm of internal rotation (IR) and external rotation (ER) were applied and CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…A previous study reported that the strain on the hip joint capsular ligament using a CT-based imaging technique showed that the ischiofemoral ligament was elongated during hip internal rotation. The length of the ischiofemoral ligament indicated the maximum length occurred at hip exion of 30°, increasing from -15° to 30°, and decreasing from 30° to 90° [18]. These anatomical data were consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study reported that the strain on the hip joint capsular ligament using a CT-based imaging technique showed that the ischiofemoral ligament was elongated during hip internal rotation. The length of the ischiofemoral ligament indicated the maximum length occurred at hip exion of 30°, increasing from -15° to 30°, and decreasing from 30° to 90° [18]. These anatomical data were consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…Recently Burkhart et al characterized the ligament strain in the hip capsule using a novel computed tomography (CT) based imaging technique. 25 Strains were calculated by comparing bead separation in loaded and unloaded conditions. For the SBILFL, strain significantly decreased in IR at 30° and 60° versus 0°.…”
Section: Resultsmentioning
confidence: 99%
“…For the IBILFL, strain decreased in IR and increased in ER with no significant position-specific differences. 25 …”
Section: Resultsmentioning
confidence: 99%
“…A previous study used a CT-based imaging technique to demonstrate that the strain on the hip joint capsular ligament was from an elongated ischiofemoral ligament during hip internal rotation. The ischiofemoral ligament length indicated that the maximum length occurred at a hip flexion of 30°, increasing from -15° to 30°, then decreasing from 30° to 90° [ 14 ]. These anatomical and biomechanical data were consistent with our findings that the ischiofemoral ligament was the primary contributor to hip stability by limiting the internal rotation between 0° and 60° of hip flexion, especially at 30°.…”
Section: Discussionmentioning
confidence: 99%